Oligoclonal bands and age at onset correlate with genetic risk score in multiple sclerosis - Harbo, Hanne F (2013)
BACKGROUND: Many genetic risk variants are now well established in multiple sclerosis (MS), but the impact on clinical phenotypes is unclear. OBJECTIVE: To investigate the impact of established MS genetic risk variants on MS phenotypes, in well-characterized MS cohorts. METHODS: Norwegian MS patients (n = 639) and healthy controls (n = 530) were successfully genotyped for 61 established MS-associated single nucleotide polymorphisms (SNPs). Data including and excluding Major Histocompatibility Complex (MHC) markers were summed to a MS Genetic Burden (MSGB) score. Study replication was performed in a cohort of white American MS patients (n = 1997) and controls (n = 708). RESULTS: The total human leukocyte antigen (HLA) and the non-HLA MSGB scores were significantly higher in MS patients than in controls, in both cohorts (P << 10 (−22)). MS patients, with and without cerebrospinal fluid (CSF) oligoclonal bands (OCBs), had a higher MSGB score than the controls; the OCB-positive patients had a slightly higher MSGB than the OCB-negative patients. An early age at symptom onset (AAO) also correlated with a higher MSGB score, in both cohorts. CONCLUSION: The MSGB score was associated with specific clinical MS characteristics, such as OCBs and AAO. This study underlines the need for well-characterized, large cohorts of MS patients, and the usefulness of summarizing multiple genetic risk factors of modest effect size in genotype-phenotype analyses.